Patofisiologi dan Manajemen Defisiensi Zat Besi pada Gagal Jantung: Sebuah Tinjauan Literatur - Laksono, Sidhi; Hertanto, Yoseph Jeffry (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
The human body needs iron to function. Deficiency of iron causes inefficient use of oxygen and decreased oxygen availability. Iron deficiency is diagnosed when serum ferritin concentration is less than 100 ng/ml or concentration of ferritin is 100-299 ng/mL with transferrin saturation less than 20% in patients with heart failure. Several possible mechanisms are proposed as a cause for iron deficiency, such as; decreased food intake, increase hepcidin secretion that causes poor iron absorption, inflammation of reticuloendothelial system that causes iron leakage and loss of blood from gastrointestinal tract. Management of iron deficiency in heart failure is focused on iron supplementation, either orally or intravenously. Oral iron supplementation is generally considered less effective and may cause severe gastrointestinal side effects. Current guidelines also support use of IV therapy. Currently, several novel therapies in development focus on iron metabolism.